2014
DOI: 10.1111/zsc.12098
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the history of an invasion: the freshwater croakers (Teleostei: Sciaenidae) in South America

Abstract: In this study, the competing hypotheses of single vs. double colonisation events for freshwater Pachyurinae (Sciaenidae) in South America is tested and the historical biogeography of the expansion of this clade within the continent is reconstructed based on phylogenetic analysis. Parsimony and Bayesian inference (BI) for 19 marine and freshwater species assigned to Sciaenidae, Haemulidae and Polypteridae were determined based on partial sequences of the mitochondrial 16S and cytochrome b genes and fragments of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
1
5
0
1
Order By: Relevance
“…This hypothesis agrees with the scenario described by Cooke et al (2012) and Boeger et al (2015) for the freshwater croaker (Plagioscion: Sciaenidae), which suggests that the migration route followed by Plagioscion was from the Amazon River to the Parana Basin. The geological history of separation and interconnection between the Amazonian and Parana systems is complex, but there are estimates that the basins split 10 million years ago with some evidence of headwater-capture events in the Parana system by the Amazon occurring within the past 10 million years (Hubert and Renno 2006).…”
Section: Historical Biogeographysupporting
confidence: 90%
See 1 more Smart Citation
“…This hypothesis agrees with the scenario described by Cooke et al (2012) and Boeger et al (2015) for the freshwater croaker (Plagioscion: Sciaenidae), which suggests that the migration route followed by Plagioscion was from the Amazon River to the Parana Basin. The geological history of separation and interconnection between the Amazonian and Parana systems is complex, but there are estimates that the basins split 10 million years ago with some evidence of headwater-capture events in the Parana system by the Amazon occurring within the past 10 million years (Hubert and Renno 2006).…”
Section: Historical Biogeographysupporting
confidence: 90%
“…We hypothesise that the landlocked population from the Uruguay River has restricted gene flow with regard to the coastal population and that this freshwater population reached its current distribution through a north-to-south continental route putatively associated with ancient connections between the Amazon and Parana basins, as occurred for Sciaenidae species (Cooke et al 2012;Boeger et al 2015). According to this scenario, L. grossidens would have reached the marine environment from the Parana basin, from which it would have expanded its distribution along the south-eastern Brazilian coast.…”
Section: Introductionmentioning
confidence: 99%
“…Such a zone occurs in estuarine areas [ 21 , 22 ] and in other transitory water bodies sometimes with limited exchange of oceanic water, like the Baltic Sea, or the inner part of fjords. Furthermore, since brackish waters repeatedly have been colonized by marine taxa, this often leads to intricate phylogenetic patterns, as has recently been revealed from several metazoan phyla [ 23 , 24 ]. Habitat shifts have played a fundamental role in the evolution of the pulmonate molluscs, which is the largest terrestrial metazoan group after insects and chordates, as they shifted from marine to terrestrial environments also through intermediate stages in intertidal and brackish waters [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The identification of haplotypes in regions where populations are native will be useful for comparison with the haplotypes present in the regions where the species are introduced. In regions where P. squamosissimus is native, few phylogenetic and biogeographic studies employing molecular markers (Cooke et al, ; Santos et al, ; Boeger et al, ) have been conducted. Avise et al .…”
Section: Collection Sites and Number Of Specimens Plagioscion Squamosmentioning
confidence: 99%
“…The identification of haplotypes in regions where populations are native will be useful for comparison with the haplotypes present in the regions where the species are introduced. In regions where P. squamosissimus is native, few phylogenetic and biogeographic studies employing molecular markers (Cooke et al, 2012;Santos et al, 2013;Boeger et al, 2014) have been conducted. Avise et al (1987) observed that mitochondrial DNA haplotypes of some of these populations have specific geographic locations, introducing phylogenetics into discussions of population structure.…”
mentioning
confidence: 99%